Do beliefs about herbicide quality correspond with actual quality in local markets? Evidence from Uganda - Ashour, Maha; Gilligan, Daniel O.; Hoel, Jessica Blumer; Karachiwalla, Naureen (Routledge, 2019)
We report the results of laboratory tests of the quality of glyphosate herbicide in Uganda and investigate whether farmers’ beliefs about the prevalence of counterfeiting and adulteration are consistent with the prevalence of low quality in their local market. We find that the average bottle in our sample is missing 15 per cent of the active ingredient and 31 per cent of samples contain less than 75 per cent of the ingredient advertised. Farmers believe 41 per cent of herbicide is counterfeit or adulterated. Beliefs are significantly correlated with quality at the local market level, but beliefs remain inaccurate, adjusting for only a fraction of actual differences in quality. Price is also significantly correlated with quality in local markets, but prices also adjust for only a fraction of quality differences.